Особливості і труднощі перекладу науково-технічних текстів - Кононенко, І. В. (ХНУРЕ, 2023)
Translation from one language to another is a complex process of human mental activity. Translation means the appropriate reproduction of a concept expressed in one language in another language, taking into account the interaction of content and form in reproducing the original text.